Robin boundary-value problem for the Beltrami equation - Gençtürk, I. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We investigate the unique solution of the Robin boundary-value problem for the Beltrami equation with constant coefficients in the unit disc by using a technique based on a singular integral operator defined on $ L_{p}(\mathbb{D})$ for all $p>2.$